Using Reading Aloud Technique to Stimulate Students Reading Comprehension - Alan Jaelani; Amalia Sadyawati; Wida Rosmawati (Tarling : Journal of Language Education, 2020)
This article aims to stimulate students' reading comprehension skills using the Reading Aloud technique. Reading aloud is the main axis connecting reading and speaking English. Reading aloud not only increases reading and basic knowledge but also improves oral expression. How the Read aloud technique can stimulate students' reading skills. Reading plays an important role as one of four abilities in improving students' English performance. This study involved 16 respondents who were 5th-semester students of the English Language Education Program at Ibn Khaldun University. This research was a descriptive study in which the researcher used a qualitative method. Data collected by interview, questionnaire, and observation. The results of the study showed that most of them did not agree with the techniques from Reading aloud. Based on respondents' statements, we found that the use of the reading method with hard reading techniques helped students to stimulate reading comprehension, especially to help students in pronunciation.